Non‐invasive assessment of liver fibrosis in C282Y homozygous HFE hemochromatosis. (4th February 2015) - Legros, Ludivine; Bardou‐Jacquet, Edouard; Latournerie, Marianne; Guillygomarc'h, Anne; Turlin, Bruno; Le Lan, Caroline; Désille, Yoann; Lainé, Fabrice; Moirand, Romain; Brissot, Pierre; Deugnier, Yves; Guyader, Dominique
Abstract Background & Aims C282Y homozygotes with serum ferritin (SF) levels >1000 μg/L and/or increased serum transaminase levels are at risk of severe F3/F4 fibrosis. Current practical guidelines recommend liver biopsy in such individuals. This prospective observational cohort study aimed to evaluate non‐invasive alternative means such as hyaluronic acid (HA) and transient elastography (TE) for the assessment of severe fibrosis in patients with SF >1000 μg/L or elevated transaminases. Methods Between September 2005 and April 2013, 77 patients diagnosed C282Y homozygotes underwent a liver biopsy because of SF >1000 μg/L and/or increased transaminases according to current guidelines, with concomitant TE. All of them had clinical and biological evaluation, including HA measurement in 52 cases. Results A total of 19.5% of patients had F3–F4 severe fibrosis. HA was higher in patients with severe fibrosis, but did not accurately predict severe fibrosis. TE was significantly higher in patients with severe fibrosis (17.2 vs. 4.9 kPa; P < 0.05) and was able to accurately predict fibrosis stage in 47/61 (77%) patients with valid measurement using a lower threshold of 6.4 kPa and an upper threshold of 13.9 kPa. Efficient assessment of severe fibrosis was not possible in patients with intermediate TE values. Conclusion An algorithm that successively employed SF and TE can accurately classify severe fibrosis in 61% of patients, restricting the need for liver biopsy to the 39% of patients with intermediate or unvalid TE values. This algorithm should be validated in independent cohorts before extended use.